DRIVING QUALITY EXCELLENCE IN PUBLIC HOUSING CONSTRUCTION: THE SYNERGISTIC EFFECTS OF OHS COMPLIANCE, HUMAN RESOURCE MANAGEMENT, AND TRANSFORMATIONAL LEADERSHIP - Dudi Mustofa; Mawardi Amin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine the effects of Occupational Health and Safety (OHS) compliance, Human Resource Management (HRM), and Transformational Leadership (TLD) on the project quality of residential building construction. The research focuses on high-rise residential building projects that present specific challenges in managing OHS, human resources, and leadership. The population includes workers, project managers, and related personnel involved in residential building construction under the Ministry of Public Works and Housing (PUPR). A purposive sampling technique was used to select 384 respondents based on their roles and direct involvement in the project. Data were analyzed using Structural Equation Modeling (SEM) to test direct and indirect relationships between variables. The results indicate that OHS, HRM, and TLD have significant positive direct effects on project quality, with standardized estimates of 0.356, 0.404, and 0.253 respectively, at a 99% confidence level. Additionally, transformational leadership also has a significant indirect effect on project quality mediated by OHS and HRM, with estimates of 0.055 and 0.060 respectively. These findings suggest that in residential building projects, transformational leadership plays a crucial role not only in directly improving project quality but also indirectly through enhancing effective OHS practices and human resource management.